A Defense of Institutional Conscience Rights for Secular Hospitals: Philosophical Justifications and Practical Applications. - Wasserman, Jason Adam; Brummett, Abram; Navin, Mark Christopher (American Journal of Bioethics, 2026)
We have previously argued that clinicians should leverage conscience, rather than quasi-objective clinical standards, to justify their refusal to provide aggressive interventions to patients who were likely permanently unconscious. Such a move sidesteps perennial disagreements over concepts such as "futility," "harm," and "best interest"; and it is consistent with the growing acknowledgement of value pluralism in healthcare. In this paper, we make similar arguments about the conscience rights of institutions. We argue that, like individuals, healthcare organizations can leverage conscience claims to justify institution-wide prohibitions on some medical interventions that are legal and within the standard of care. Of course, faith-based healthcare institutions already enjoy institutional conscience protections. We argue that secular institutions can also claim conscience protections to refuse some kinds of interventions on the basis of system-level moral commitments.